Ability to Identify Persuasive Sentences in Negotiation Texts Using Learning Models Cooperative Integrated Reading And Composition (CIRC) Class X Students of SMK Negeri 1 Batang Angkola - Aritonang, Devinna Riskiana (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This research is entitled